INTERNET COGNITIVE BEHAVIOR THERAPY FOR POSTPARTUM DEPRESSION - Anita Dwi Rahmawati (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Background: Postpartum depression (PPD) occurs in 25-50% of those affected with 10-15% of postpartum mothers each year having depressive symptoms that last more than 6 months. PPD is an important public health issue because of its chronic and long-term effects that have significant detrimental effects on mothers, their families, and their child's development. The primary treatments for PPD have included psychological interventions such as physical counseling, interpersonal psychotherapy (IPT), cognitive behavior training (CBT), and problem-focused counseling. However, there is no information about how efficient and suitable these approaches are for postpartum depression. Objective: This study aimed to examine the efficacy of internet cognitive behavior therapy for postpartum depression.Methods: A systematic review is a method of study. An extensive search was conducted in Google Scholar, ScienceDirect, Medline, andPubMed to locate detailed indexed articles. The search included articles published, in the last 5 years, from 2015 to 2020. Results: All 5 studies were Randomized Controlled Trials (RCT) studies, with a total of 481 participants. PPD measurements using self-evaluation scales for depression and structured clinical interviews. Three studies used application programs are MumMoodBooster and one study used Therapist and Be a Mom combined CBT program.Conclusion: The study looked at the impact of internet CBT on PPD reduction. When compared to the TAU (control group), the findings of this 5 study showed that internet CBT could lower the EPDS score of all mothers in the intervention group (iCBT). Keywords: cognitive behavior therapy, depression, postpartum.